Cardiac shear wave elastography can detect the presence of a septal scar in patients with LBBB. (3rd October 2022) - Wouters, L; Duchenne, J; Bezy, S; Papangelopoulou, K; Puvrez, A; Klop, B; Voros, G; D'hooge, J; Voigt, J U
Abstract: Background: In patients with heart failure and a left bundle branch block (LBBB), cardiac resynchronization therapy (CRT) is an established treatment. However, the rate of non-response to this costly therapy remains high. So far, CRT has proven to be less effective in patients with a septal scar. Detection of a septal scar before CRT implantation could therefore help to improve response rate to CRT. The gold standard to detect septal scarring, LGE MRI, is quite costly and not suited or available for all patients. Cardiac shear wave elastography (SWE) may be an alternative. It allows for the non-invasive assessment of myocardial stiffness based on the detection of shear waves, after for example mitral valve closure (MVC). SWE has shown to be capable to detect myocardial scar, however this has never been demonstrated in the presence of LBBB. Purpose: To determine whether SWE is able to detect the presence of a septal scar in patients with LBBB. Methods: To investigate this, 39 CRT patients with a LBBB were included with ischemic (n=10; age: 73±6 y; 70% males) or non-ischemic (n=29; 68±14 y; 52% males) cardiomyopathy and 9 age-matched healthy volunteers (68±4 y; 55% males) served as controls. In order to obtain native ventricular conduction biventricular (BiV) pacing was turned off. All ischemic patients had septal scar only, proven by MRI or scintigraphy. For SWE, left ventricular parasternal long-axis views were acquired with an experimental high frame rate ultrasound scanner (frame rate: 932±32 fps). Shear waves were visualized in M-modes of the septum, colour coded for tissue acceleration. The slope of the shear waves in the M-mode represents their propagation speed (Figure 1A). Results: Patients characteristics and echocardiographic parameters are shown in Table 1. Shear wave speed after MVC was significantly higher in LBBB patients with and without a septal scar compared to healthy controls (7.8±1.2 m/s vs 4.5±1.1 m/s; p<0.001; 5.6±1.1 m/s vs 4.5±1.1 m/s; p=0.041; Figure 1B), indicating that the presence of LBBB increases myocardial stiffness. However, more importantly, shear wave speed was significantly higher in LBBB patients with a septal scar compared to LBBB patients without a septal scar (7.8±1.2 m/s vs 5.6±1.1 m/s; p<0.001; Figure 1B). This implies that the presence of a septal scar increases shear wave speed even more than LBBB alone. A ROC-curve analysis further showed that SWE is capable of distinguishing scarred from non-scarred septum in LBBB patients (AUC: 0.92; p<0.001; Figure 1C). A cut-off of 7.1 m/s could identify LBBB patients with a septal scar with a sensitivity of 80% and specificity of 93%. Conclusion: Septal scarring results in a significant increase in myocardial stiffness, so that it reaches a clear pathological range. SWE seems therefore capable of detecting the presence of a septal scar in LBBB patients and could potentially be used as a novel approach for the assessment of septal scarring in CRT candidates. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Research foundation Flanders (FWO)